The Influence of the Intermittent Behavior of the Nocturnal Atmospheric Flow on the Prediction of the Diurnal Temperature Range: A Simplified Model Analysis - Leandro L. Gonzales; Felipe D. Costa; Otávio C. Acevedo; Daniel M. dos Santos; Luiz E. Medeiros; Arlindo D. Carvalho Junior; Franciano S. Puhales; Vagner Anabor; Luis G. N. Martins; Giuliano Demarco; Gervásio A. Degrazia (Advances in Meteorology)
The variation of the atmospheric temperature near the surface associated with anthropogenic effects is analyzed using a simplified atmospheric model. Local changes in cloud cover and four different scenarios of atmospheric concentration of carbon dioxide are considered. The results show that the highest temperature variability occurs in the weak wind and decoupled state and in the transition between flow regimes. In agreement with previous efforts, the results indicate that the reduction of diurnal temperature range is related to the existence of two distinct flow regimes in the stable boundary layer. However, in the decoupled state, the occurrence of intermittent bursts of turbulence may cause temperature variations among the different scenarios to become unpredictable. It implies that it is difficult to predict the diurnal temperature range in places where low winds are common.